2013
DOI: 10.1016/j.phrs.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of choline transporter-like protein 1 (CTL1) in small cell lung carcinoma cells: A target molecule for lung cancer therapy

Abstract: Choline is essential for the synthesis of the major membrane phospholipid phosphatidylcholine and the neurotransmitter acetylcholine (ACh). Elevated levels of choline and up-regulated choline kinase activity have been detected in cancer cells. Thus, the intracellular accumulation of choline through choline transporters is the rate-limiting step in phospholipid metabolism and a prerequisite for cancer cell proliferation. However, the uptake system for choline and the functional expression of choline transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 50 publications
3
42
1
Order By: Relevance
“…Increased expression of CHT1 and CTL1 in other cancers has been previously reported (10, 13, 14). Other choline transporters and phospholipases (7) may also have contributed to the altered choline metabolism and should be further investigated.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Increased expression of CHT1 and CTL1 in other cancers has been previously reported (10, 13, 14). Other choline transporters and phospholipases (7) may also have contributed to the altered choline metabolism and should be further investigated.…”
Section: Discussionsupporting
confidence: 55%
“…Increased expression of the high-affinity choline transporter CHT1 with a K m of ~ 2 µM, also called solute carrier family 5 member 7 (SLC5A7) (12), has been previously observed in breast cancer cells (10). Another choline transporter, choline transporter-like protein 1 (CTL1) with a K m of ~ 68 µM, was found to be overexpressed in human lung and colon carcinoma cells (13, 14). …”
Section: Introductionmentioning
confidence: 99%
“…Notably, the SLC44A1-5 family has been shown to be functionally important in the development of human lung, prostate and colon carcinoma (17)(18)(19)(20), however, the mechanisms underlying the effects of the SLC44A1-5 family remain to be elucidated. One of these proteins, SLC44A1, has previously been found to stimulate NCI-H69 cell growth and choline uptake, suggesting that SLC44A1 may function as a lung carcinogenic gene (17).…”
Section: Discussionmentioning
confidence: 99%
“…One of these proteins, SLC44A1, has previously been found to stimulate NCI-H69 cell growth and choline uptake, suggesting that SLC44A1 may function as a lung carcinogenic gene (17). The possible correlation between choline uptake and viability was also assessed (the effect of choline transporter inhibitors on the survival of various cancer cells).…”
Section: Discussionmentioning
confidence: 99%
“…The choline analog hemicholinium-3 (HC-3) and tetrahexylammonium chloride were reported to inhibit choline uptake and reduce cell proliferation when treating the human colon carcinoma cell line HT-29 (144). The Na + /H + exchanger inhibitor dimethylamiloride and various organic cations such as quinine, quinidine, desipramine, imipramine, clomipramine, diphenhydramine, and fluvoxamine, among others were shown to inhibit choline uptake and cell viability in the small cell lung carcinoma cell line NCI-H69 (145). In the same study, HC-3 and CTL1 siRNA were shown to inhibit choline uptake and cell viability as well, along with increasing caspase-3/7 activity (145).…”
Section: Choline Transportersmentioning
confidence: 99%